A Parasitoid Muscidifurax raptor Girault & Sanders (Insecta: Hymenoptera: Pteromalidae): EENY-657/IN1161, 5/2016 - Tucker, Nicholas S.G.; Kaufman, Philip E. (EDIS, 2017)
Includes: Introduction - Synonymy - Distribution - Life Cycle and Description - Hosts - Economic Importance - Selected References Previously published on the Featured Creatures website at http://entnemdept.ufl.edu/creatures/BENEFICIAL/WASPS/Muscidifurax_raptor.htm